Office Of The Accountant General Of The Federation (OAGF) Examines The Effects Of Effective Leadership And Strategies In Nigeria. - Ajiteru,S.A.R; Sulaiman T.H; Abalaka, J.N (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
The research paper Examining the leadership of the Office of the Accountant General of the Federation (OAGF), it is evident that the country is in trouble and need a leader capable of bringing out the best in Nigerian supporters and guiding the country toward stability. The next logical step after gathering data is research analysis. Both the main data gathered from the in-person interviews and the data already available from public sources spanning the 50-year study period were analyzed using the constant comparative approach (Merriam, 2019). This clarified the qualitative case study technique utilized in the research design, which examined the influence of leadership on the governance of infrastructure development in Nigeria between 1960 and 2020. This leader needs to be dependable, emotionally knowledgeable, firm, prepared to endure hardships for the country, committed to bridging ethnic divides, and able to instill hope in the populace. leader must be able to process a variety of information and find effective solutions to challenging issues. This essay embraces the idea that leadership entails a leader or leaders, followers, and a social influence process. This viewpoint is influenced by clinical psychology socio-emotional intelligence and social psychology concepts of social influence; as a result, leadership for Nigeria will be examined from these angles.